Application of Levi’s Muscle Index in frailty assessment: comparison of bioimpedance measures among older adults - Lafontant, Kworweinski; Fukuda, David H.; Zamarripa, Estefania; Tice, Abigail L.; Suarez, Jethro Raphael M.; Banarjee, Chitra; Kim, Dahee; Stout, Jeffrey R.; Park, Joon-Hyuk; Xie, Rui; Thiamwong, Ladda (Frontiers in Medicine, 2025)
IntroductionFrailty is prevalent among older adults and is characterized by reductions in physical function and muscle quality. Despite the emerging clinical utility of bioelectrical impedance analysis (BIA) and phase angle (PhA) as a bioimpedance index, little is known about how bioimpedance indices such as Levi’s Muscle Index (LMI), reactance/height (Xc/Height), and resistance/height (R/Height), relate to physical function and frailty.MethodsThis cross-sectional study examined 208 community-dwelling older adults (female, n = 183; age = 74.2 ± 6.9 years; BMI = 30.4 ± 6.4 kg/m2) to compare physical function measures and bioimpedance indices across frailty categories determined by the FRAIL questionnaire. PhA, LMI, Xc/Height, and R/Height were all assessed at 50 kHz using a direct segmental multi-frequency InBody s10 BIA device. Physical function was assessed using handgrip strength, postural sway, Timed-Up-and-Go, and the Short Physical Performance Battery. Data were analyzed using Spearman rho (ρ) and Pearson r correlation coefficients, and group differences were examined using Kruskal-Wallis H tests and one-way ANOVA.ResultsPhA (r = −0.18, p = 0.01) and Xc/Height (r = −0.24, p < 0.001) were significantly associated with FRAIL scores. LMI and PhA were well correlated with each other (ρ = 0.76, p < 0.001), yet Xc/Height was the only bioimpedance index to significantly differ between frailty categories (F = 6.39, p = 0.002, ηp2 = 0.06).ConclusionResults suggest Xc/Height may be the only bioimpedance index indicative of frailty among older adults. Given the variety of assessments used to categorize frailty, these conclusions may be limited to the use of the FRAIL questionnaire; future research should compare LMI and PhA using multiple frailty indices.